Implementasi Sistem Informasi Pemerintahan Daerah (SIPD) pada Pemerintah Kecamatan Sumbang Kabupaten Banyumas - Nanda Yoga Aditiya; Popy Dian Indira Kusuma (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
In creating accurate information, the Ministry of Home Affairs launched an application, namely the Regional Government Information System (SIPD), which is contained in Minister of Home Affairs Regulation Number 70 of 2019, this application is useful for achieving or measuring success in coordinating between the Central Government and Regional Governments. synergize with each other in creating accurate and accountable information. This research aims to determine the extent to which the implementation of the Regional Government Information System (SIPD) application in the Sumbang District Government, Banyumas Regency can be used properly. This research uses qualitative research methods with data collection techniques carried out using interview, observation and documentation methods. The object of this research is Regional Government. This research uses Edward III's theory in the form of Communication, Human Resources (HR), disposition and bureaucratic structure. This theory is used to see the obstacles experienced in implementing the Regional Government Information System (SIPD) application. The results of the analysis of the implementation of the Regional Government Information System (SIPD) in the Sumbang District Government, Banyumas Regency, of the four indicators in Edward III's theory are running in accordance with existing regulations and are significant. The obstacles that occur are influenced by applications that often experience problems with errors and system traffic. The benefit of the regional government information system (SIPD) application is that the regional financial planning process is easier to carry out because it is in an electronic system. Uniforming regional financial planning and governance processes, optimizing main activities and facilitating supervision and audits.